2013
DOI: 10.1063/1.4807134
|View full text |Cite
|
Sign up to set email alerts
|

Polyamorphism and origin of spatially heterogeneous dynamics in network-forming liquids under compression: Insight from visualization of molecular dynamics data

Abstract: Polyamorphism and dynamical heterogeneities in network-forming liquids (SiO2, GeO2, Al2O3) at 3200 K and in a wide pressure range are investigated by molecular dynamics simulation. Results show that their structure comprises three structural phases: TO4-, TO5-, and TO6-phases (T = Si, Ge, or Al). The size of structural phase regions significantly depends on compression. Besides, the mobility of atoms in different structural phases is different. For SiO2 and GeO2 systems, the TO5-phase forms mobile regions. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…of SiO x -phases (SiO x -domain) in 3D space is shown in Figure 2. The phase separation and forming the regions with different structures (polyamorphism) also has been referred in previous works [34,35,50]. However, the previous works have not calculated the size distribution of clusters (phase regions).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…of SiO x -phases (SiO x -domain) in 3D space is shown in Figure 2. The phase separation and forming the regions with different structures (polyamorphism) also has been referred in previous works [34,35,50]. However, the previous works have not calculated the size distribution of clusters (phase regions).…”
Section: Resultsmentioning
confidence: 98%
“…Liquid-liquid phase transition, which results in the regions with different densities in liquid system as temperature or pressure are varied. Namely, the phase transition from low density (LD) to high-density (HD) form has also been shown by experiments and molecular dynamics simulation [5,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] for H 2 O, Si, SiO 2 , Al 2 O 3 -Y 2 O 3 , . .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The regions between the magenta arrows mark HS+RS phase coexistence and the region between the brown arrows marks the RS+TS phase. As is already known, the existence of several high- and low-density ground states is a characteristic property of network-forming liquids. , …”
Section: Determination Of the Phase Diagrammentioning
confidence: 95%
“…The voids created a very large hole with a volume five times bigger than that of the aluminum atom. Other simulations [24,25] showed that the phase regions of liquid Al2O3 strongly depend on compression. The mobility of atoms in different phases is different; the AlO6-phase forms immobile regions.…”
Section: Introductionmentioning
confidence: 96%